2022
DOI: 10.1002/ca.23881
|View full text |Cite
|
Sign up to set email alerts
|

Adductor longus: An anatomical study to better understand groin pain

Abstract: We investigated the shear modulus-passive force relationship in the hip adductor longus (AL) muscles of human cadavers and explored the effect of muscle architecture on the elastic properties of the AL muscle using shear wave elastography (SWE).Nine AL muscles were harvested from a soft, embalmed cadaver. The AL muscles were affixed to a custom-built device comprising two clamps, a pulley, and a cable to provide passive loads, which were increased from 0 to 600 g in 60-g increments. The shear modulus of the AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…This study demonstrated that the shear modulus of the AL muscle increases through hip abduction, extension, and internal rotation. We have already demonstrated a strongly linear relationship between the shear modulus and passive force in the AL muscle 16 . Therefore, the results of the present study indicate that the passive force of the AL muscle can be increased by hip abduction, extension, and internal rotation.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…This study demonstrated that the shear modulus of the AL muscle increases through hip abduction, extension, and internal rotation. We have already demonstrated a strongly linear relationship between the shear modulus and passive force in the AL muscle 16 . Therefore, the results of the present study indicate that the passive force of the AL muscle can be increased by hip abduction, extension, and internal rotation.…”
Section: Discussionmentioning
confidence: 68%
“…In this study, it was unclear whether the AL muscle had a hip internal or external rotation moment arm because the hip rotation moment arm of each subject was not measured. However, a previous study showed a strong linear relationship between the shear modulus of the AL muscle and the passive force 16 . At 20° hip extension, therefore, there might be a passive force in the AL muscle due to the stretching of the AL muscle by hip internal rotation.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations